Restorative Justice in Minor Criminal Cases: A Study of Tanjung Balai District Court Decision No. 1/Pid.C/2023/PN Tjb - Dias Lutfiyansyah; Boedi Prasetyo (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The dominance of the retributive paradigm in the Indonesian criminal justice system has often failed to achieve substantive justice, particularly in addressing minor offenses arising from structural poverty. This study aims to analyze the implementation of restorative justice in Tanjung Balai District Court Decision Number 1/Pid.C/2023/PN Tjb and to examine the legal reasoning underlying the court’s adoption of this mechanism. The study employs a normative legal research method using statutory, conceptual, and case approaches, with qualitative analysis conducted through a descriptive-prescriptive framework. The findings indicate that restorative justice was implemented through mediation involving the offender, the victim, and the community, resulting in the restoration of social relationships and a more proportionate resolution of the dispute. The judge’s legal considerations were based on an integration of juridical, philosophical, and sociological dimensions, particularly the offender’s economic circumstances and the pursuit of substantive justice. This study demonstrates that the decision constitutes a form of progressive jurisprudence, reflecting a paradigm shift in criminal law enforcement from a retributive orientation toward a restorative approach.